2020
DOI: 10.1177/1470320320966445
|View full text |Cite
|
Sign up to set email alerts
|

The role of renin-angiotensin system in patients with left ventricular assist devices

Abstract: End-stage heart failure is a condition in which the up-regulation of the systemic and local renin-angiotensin-aldosterone system (RAAS) leads to end-organ damage and is largely irreversible despite optimal medication. Left ventricular assist devices (LVADs) can downregulate RAAS activation by unloading the left ventricle and increasing the cardiac output translating into a better end-organ perfusion improving survival. However, the absence of pulsatility brought about by continuous-flow devices may variably tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…In humans, there is continued tissue RAAS activation after various surgical interventions, 22 , 23 with some reports concluding that pharmacological blockade of RAAS after cardiovascular surgeries is prognostically beneficial. 9 , 16 , 17 , 24 , 25 , 26 Since the current study focused on the systemic instead of local components of RAAS, results of tissue RAAS evaluation could be different but were not evaluated. We do currently believe that no further recovery in the cardiovascular system is required for our dogs.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there is continued tissue RAAS activation after various surgical interventions, 22 , 23 with some reports concluding that pharmacological blockade of RAAS after cardiovascular surgeries is prognostically beneficial. 9 , 16 , 17 , 24 , 25 , 26 Since the current study focused on the systemic instead of local components of RAAS, results of tissue RAAS evaluation could be different but were not evaluated. We do currently believe that no further recovery in the cardiovascular system is required for our dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, risk reduction for stroke, pump thrombosis, and gastrointestinal bleeding from arteriovenous malformation have been described by renin-angiotensin-aldosterone inhibition on LVAD. 23 Currently, the relevance of the individually suggested recovery mechanisms is not clear. An interplay of many mechanisms was suggested to cause both remodeling and its reversal with or without VAD support.…”
Section: Cardiac Recovery: Definitions and Potential Pathomechanismsmentioning
confidence: 99%
“…A detailed description has been subject of several reviews. 17 , 22 , 23 , 24 In addition to strictly cardiac effects, it has been shown that VAD support decreases inflammation-mediated myocardial injury by reducing the level of plasma cytokines and production of autoantibodies against cardiac proteins level. 24 Furthermore, it has been shown that VAD support itself can downregulate the pathologically upregulated renin–angiotensin–aldosterone and sympathetic nervous systems.…”
Section: Cardiac Recovery: Definitions and Potential Pathomechanismsmentioning
confidence: 99%
See 2 more Smart Citations